Remote detection of fungal pathogens in viticulture using laser-induced fluorescence: an experimental study on infected potted vines - Kölbl, Christoph; Diedrich, Manu; Ellingen, Elias; Duschek, Frank; Selim, Moustafa; Berkelmann-Löhnertz, Beate (Frontiers in Horticulture, 2023)
Pathogenic fungi, like Plasmopara viticola and Erysiphe necator, severely threaten the annual yield of grapes in quantity and quality. Compared to other crops, fungicides are intensively applied in viticulture for countermeasure. The goal of precision viticulture is to optimize vineyard performance as well as the environmental impact by reducing fungicides and applying different techniques and combined strategies. Therefore, new emerging technologies are required including non-invasive detection, as well as monitoring and tools for early and in-field detection of fungal development.In this study, we investigated leaves of potted vines (Vitis vinifera cv. Riesling) and traced the development of the inoculated leaves using our new remote detection system vinoLAS ® , which is based on laser-induced fluorescence spectroscopy. We ran a measurement campaign over a period of 17 days and we were able to detect a leaf infection with P. viticola, the causal agent of downy mildew, between 5 and 7 days after inoculation. Our results provide evidence for a successful application of laser-based stand-off detection in vineyard management in the future. Thus, the vinoLAS system can serve as a model technology for detection of pathogenic disease symptoms and thus monitoring complete vineyard sites. This allows early countermeasures with suitable crop protection approaches and selected hot-spot treatment. As P. viticola is considered one of the most damaging fungi in European viticulture, disease mapping via this monitoring tool will help to reduce fungicide applications and will, therefore, support implementation of the European Green Deal claims.